(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Tension-type headache (TTH) is one of the most common primary headache disorders in adolescents, representing a major cause of reduced academic performance, impaired quality of life, and psychosocial difficulties. This study aims to review the prevalence, risk factors, and clinico-neurological features of TTH in adolescent populations. Literature was reviewed from PubMed, Scopus, and Google Scholar, focusing on studies published between 2005 and 2025. Findings indicate that TTH prevalence among adolescents ranges from 15% to 35%, with higher rates in females. Identified risk factors include psychological stress, poor sleep hygiene, prolonged screen exposure, musculoskeletal tension, and family history of headache disorders. Clinically, TTH is characterized by bilateral, pressing, or tightening pain of mild to moderate intensity, which is not aggravated by routine physical activity, and is often accompanied by tenderness in the pericranial muscles. Neurological examination is typically normal, though somatic comorbidities such as sleep disturbances, anxiety, and mood disorders are common. Understanding these clinical and epidemiological features is crucial for timely diagnosis, effective preventive strategies, and optimal management in adolescent patients.